Reactive hot pressing and mechanical properties of TiAl3/Ti3AlC2/Al2O3 in situ composite - Chen, Weiping; Xiao, Huaqiang; Fu, Zhiqiang; Fang, Sicong; Zhu, Dezhi (Materials in engineering, 2013)
Dense TiAl3/Ti3AlC2/Al2O3 composites were synthesised from Al, TiO2 and TiC powder mixtures at 1250 C and 50 MPa for 10 min using an in-situ reaction/hot-pressing method. The reaction kinetics, microstructure, mechanical properties and toughening mechanism of the fabricated composites were investigated. TiO was a transitional phase, and a reaction path for the Al/TiO2/TiC system was proposed. The composites achieved Vickers hardness, three-point bending strength and fracture toughness values of about 8.4 GPa, about 658.9 MPa and about 7.9 MPa.m1/2, respectively. Analysis of microstructure/crack propagation path interaction revealed that crack deflection, crack bridging, and Ti3AlC2 particle pullout were the main mechanisms responsible for toughening. The compressive strength of the in-situ composites was much higher than that of as-cast TiAl3 and was maintained even at 1000 C due to the cooperative strengthening introduced by Ti3AlC2 and Al2O3.